Comparative Study of Fear and Anxiety of COVID-19 on Families with and without Members in Foreign Lands - Giri, Sagarananda; Dangi , Nim Bahadur; Nepal , Sushil; Gurung, Anupa; Timilsina , Kailash; Subedi , Sapana; Pokhrel , Shiwani; Gautam, Sangita; Kunwar , Laxmi (Europasian Journal of Medical Sciences, 2024)
Background: Pandemics initially produce overwhelming feelings of anxiety and uncertainty, which can escalate into stress, worry, and melancholy, potentially leading to societal unrest and mental illness. Families relying solely on remittances are particularly vulnerable to psychological stress. This study aims to assess the impact of COVID-19 related fear and anxiety in households with and without members living abroad.Methods: A web-based cross-sectional survey was conducted among family heads aged 18 years and older who provided oral consent in Pokhara, Nepal. Anxiety was assessed using the Generalized Anxiety Assessment (GAD-7), and Fear was measured using the Fear of COVID-19 Scale (FC-19S).Results: Age and having family members abroad were significantly associated with fear of COVID-19. Similarly, age and family members abroad were significantly associated with anxiety. Younger individuals (55 years) (OR = 2.294, p = 0.015). Conversely, individuals older than 54 years were 2.1 times more likely to experience anxiety compared to the younger population (OR = 2.168, p = 0.023).Conclusion: The findings highlighted age and family members living abroad as significant factors in fear and anxiety. The study underscores the need for mental health and psychosocial support services to be integrated into community healthcare, particularly during pandemics, to address these challenges effectively.